A sensitive and high throughput bacterial luminescence assay for assessing aquatic toxicity – the BLT-Screen. Issue 5 (7th April 2015) - van de Merwe, Jason P.; Leusch, Frederic D. L.
Abstract : The development of a cost effective, sensitive and high throughput aquatic toxicity assay with a wide range of research and monitoring applications. Abstract : Bioassays using naturally luminescent bacteria are commonly used to assess the toxicity of environmental contaminants, detected by a decrease in luminescence. Typically, this has involved the use of commercial test kits such as Microtox and ToxScreen. These commercial assays, however, have limitations for routine environmental monitoring, including the need for specialized equipment, a low throughput and high on-going costs. There is therefore a need to develop a bacteria bioassay that is sensitive, high-throughput and cost effective. This study presents the development and application of the BLT-Screen (Bacterial Luminescence Toxicity Screen), a 96-well plate bioassay using Photobacterium leiognathi . During development of the method, the concentration of the phosphate buffer in the experimental medium was adjusted to maximize the sensitivity of the assay, and protocols for analyzing both solid-phase extracts and raw water samples were established. A range of organic compounds and metals were analyzed in the assay, as well as extracts of various water samples, including drinking water, wastewater effluent and river water. The IC50 values of the organic compounds and metals tested in the BLT-Screen were comparable to previously published ToxScreen and Microtox data. In addition, the assay was sensitive enough to detect toxicity in all water types tested, and performed equally well for both solid-phase extracts and raw water samples. The BLT-Screen therefore presents a cost-effective, sensitive and high throughput method for testing the toxicity of environmental contaminants in a range of water types that has widespread applications for research, as well as for routine monitoring and operation of wastewater and drinking water plants.